1998
DOI: 10.1021/es980028z
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Modeling of the Diurnal Cycling of Atmospheric PCBs and PAHs

Abstract: PCBs and PAHs were quantified in air samples taken every 6 h over a 7 day period in August 1995 at a rural site in northwest England. For the first 5 days, a stable high-pressure system moved slowly across northern England from the east. During this time, PCB air concentrations responded very closely to the changes in ambient temperature, following a clear diurnal cycle. All PCB congeners correlated well with temperature, but the correlation was strongest for lower chlorinated species. Daily PCB concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
108
2
11

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 27 publications
15
108
2
11
Order By: Relevance
“…While average temperatures between the locations varied between 768 and 898F, a linear regression suggested that PAS response was unrelated to temperature for all locations (r 2 =0). This finding is supported by previous studies showing no significant trends between temperature and PAS response or PAH concentrations under normal environmental conditions Lee et al, 1998). Wilson et al (1994) also reports that PAS response was unaffected by relative humidity.…”
Section: Variability Due To Physical Parameterssupporting
confidence: 86%
“…While average temperatures between the locations varied between 768 and 898F, a linear regression suggested that PAS response was unrelated to temperature for all locations (r 2 =0). This finding is supported by previous studies showing no significant trends between temperature and PAS response or PAH concentrations under normal environmental conditions Lee et al, 1998). Wilson et al (1994) also reports that PAS response was unaffected by relative humidity.…”
Section: Variability Due To Physical Parameterssupporting
confidence: 86%
“…Studies by Lee et al (2000Lee et al ( , 1998 have reported that OCPs and other SOCs followed clear diurnal cycles for the first 5 days of their study when the stable atmospheric conditions were dominant. However, for the last 2 days as a more unstable and cooler weather started to influence the sampling site, OCP concentrations were controlled primarily by advection (Lee et al, 2000).…”
Section: Effect Of Meteorological Parameters On Gas-phase Ocp Concentmentioning
confidence: 98%
“…As the temperature rises, gas-phase air concentrations increase as a result of volatilization from previously contaminated surfaces such as soil, atmospheric particles, water, and vegetation. Short-term studies have indicated that ambient gas-phase SOCs also respond to short-term temperature changes resulting in rapid movement between environmental compartments (i.e., diurnal cycling) (Lee et al, 1998(Lee et al, , 2000. Advection and ongoing sources are other important factors affecting the variation of ambient gas-phase OCP concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This was the first time that such a diel cycle had been reported over the open ocean. Diel cycles had previously been observed in several studies on land (e.g., [8][9][10][11][12][13][14]); however, high daytime concentrations were usually associated with high daytime temperatures, which were not observed in the cycle over the ocean. Jaward et al [6] hypothesized that interactions between plankton and the dissolved phase may play a role in their observations, but stated that further measurement data were needed to evaluate this hypothesis.…”
Section: Introductionmentioning
confidence: 79%